Entrepreneur from alumni / Priestly Lanting Layang ... [et al.] - Layang, Priestly Lanting; Abang Shamsudin, Dayang Nurul Amieyda; Herman, Nurul Izzah; Standard, Stephanie Sonia; Mokhtar, Muhammad Adib Azfar (Perpustakaan Tun Abdul Razak, 2023)
It was at Imperial where he developed Freevolt, a patented wireless charging technology capable of recharging batteries from energy from mobile phones and other sources. But, as his PhD came to an end, he wasn’t sure what to do next. He had a few options including returning to America or selling to investors.